Association between a single mother family and childhood undervaccination, and mediating effect of household income: a nationwide, prospective birth cohort from the Japan Environment and Children's Study (JECS) - Hiroyuki Kuroda; Atsushi Goto; Chihiro Kawakami; Kouji Yamamoto; Shuichi Ito; Japan Environment and Children's Study (JECS) (BMC, 2022)
Abstract Background Although childhood undervaccination among single mother families is a concern for child healthcare, their association is still under debate. This study aimed to investigate the association between maternal marital status and the risk of childhood undervaccination and determine the mediating effect of household income. Methods We utilised prospective birth cohort from the Japan Environment and Children's Study (JECS). Of 104,062 foetal records (children) from 97,413 mothers, 82,462 that included mothers recruited between 2011 and 2014, were analysed. Childhood undervaccination was defined as not having been vaccinated with at least one routine vaccine. A log-binomial regression analysis was used to estimate the risk ratio (RR) for the association between maternal marital status and the risk of childhood undervaccination. A causal mediation analysis was further performed to investigate the proportion of the association mediated by household income. Results Among 82,462 children, 3188 and 79,274 had unmarried and married mothers, respectively. Childhood undervaccination was observed in 1053 (33.0%) and 16,901 (21.3%) children of unmarried and married mothers, respectively. Maternal marital status was associated with a higher risk of childhood undervaccination (adjusted risk ratio [aRR], 1.34; 95% confidence interval [CI], 1.27 to 1.41). Compared with married and older mothers, both unmarried and older (aRR, 1.54; 95% CI, 1.35 to 1.77) and unmarried and younger (aRR, 1.66; 95% CI, 1.54 to 1.79) mothers were associated with a higher risk of childhood undervaccination. The causal mediation analysis showed that the proportion mediated by household income was 10.5% (95% CI, 9.9 to 11.0%). Conclusions This nationwide, prospective, large-scale birth cohort study found that a household with a single mother was associated with an increased risk of childhood undervaccination, and 10% of this association was explained by household income. These findings underscore the importance of improving the social environment among single mother families, including not only poverty but also working conditions.